Assessment and Evaluation in Language Learning: Bridging Theory and Practice - Mishra, Priyanka (Journal of Advanced Research in English & Education; Vol 9 No 4 (2024): Journal of Advanced Research in English and Education, 2024)
Assessment and evaluation are fundamental components of language learning and teaching, influencing both learners’ progress and instructional strategies. These processes are integral to measuring learners’ language proficiency, providing feedback, and guiding future learning activities. This review article explores the theoretical foundations and practical applications of assessment and evaluation in language learning, highlighting the evolving landscape of language assessment methods and their impact on educational outcomes. The paper delves into the relationship between assessment and language acquisition, emphasizing how different assessment methods reflect theories of language learning and cognitive development. It discusses various types of assessments, including diagnostic, formative, summative, and dynamic assessments, and their specific roles in supporting language acquisition. The paper also examines the intricate roles of formative and summative evaluations in the language learning process, highlighting the benefits and limitations of each approach in promoting learner progress. Furthermore, it addresses the challenges faced by educators in implementing effective assessments, such as ensuring fairness, addressing cultural diversity, and integrating technology in assessment practices. The article also explores how recent innovations in assessment, such as performance-based and task-based assessments, align with communicative language teaching principles and provide more comprehensive insights into learners’ ability to use language in real-world contexts. It concludes by offering recommendations for bridging the gap between theory and practice in the field of language learning, advocating for a more integrated and inclusive approach to assessment that takes into account the diverse needs of learners, the role of feedback, and the increasing significance of digital tools.